2014
DOI: 10.1186/1471-2164-15-4
|View full text |Cite
|
Sign up to set email alerts
|

Specific gene-regulation networks during the pre-implantation development of the pig embryo as revealed by deep sequencing

Abstract: BackgroundBecause few studies exist to describe the unique molecular network regulation behind pig pre-implantation embryonic development (PED), genetic engineering in the pig embryo is limited. Also, this lack of research has hindered derivation and application of porcine embryonic stem cells and porcine induced pluripotent stem cells (iPSCs).ResultsWe identified and analyzed the genome wide transcriptomes of pig in vivo-derived and somatic cell nuclear transferred (SCNT) as well as mouse in vivo-derived pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 54 publications
7
155
0
Order By: Relevance
“…1B). Consistent with the previous RNA sequencing data (Cao et al, 2014), RT-PCR results confirmed the absence of two other CDX family members, CDX1 and CDX4 (three technical replicates, Fig. S1C).…”
Section: Cdx2 Spatiotemporal Expression Pattern In Early-stage Porcinsupporting
confidence: 78%
“…1B). Consistent with the previous RNA sequencing data (Cao et al, 2014), RT-PCR results confirmed the absence of two other CDX family members, CDX1 and CDX4 (three technical replicates, Fig. S1C).…”
Section: Cdx2 Spatiotemporal Expression Pattern In Early-stage Porcinsupporting
confidence: 78%
“…Before implantation, embryonic phenotypes for loss-offunction mutation of the pathway are not detected (20). Transcriptome sequencing and analyzing pig embryos in vivo and in vitro also show that the TGF␤ pathway is not active well before maternal zygotic transition at the four-to eight-cell stages (25). Those data suggest the function of the TGF␤ pathway is suppressed during early embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…After passing quality control, the RNA was treated and sequenced by the Novogene Bioinformation Institute as previously described (28). The RNAsequencing (RNA-Seq) data have been submitted to the National Center for Biotechnology Information Sequence Read archive (accession number: SRP052846, http://www.ncbi.nlm.nih.gov/sra).…”
Section: Rna Sequencingmentioning
confidence: 99%